2021
DOI: 10.1177/2333393621993450
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Nurses’ Professional Practices to Prevent, Recognize, and Respond to Suspected Child Maltreatment in Home Visiting: An Interpretive Descriptive Study

Abstract: The purpose of this analysis was to understand public health nurses’ experiences in preventing and addressing suspected child maltreatment within the context of home visiting. The principles of interpretive description guided study decisions and data were generated from interviews with 47 public health nurses. Data were analyzed using reflexive thematic analysis. The findings highlighted that public health nurses have an important role in the primary prevention of child maltreatment. These nurses described a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Specifically in women's care, midwives and health visitors perceive collaboration to be useful across the continuum of service delivery from antenatal care to postnatal care (Aquino et al, 2016). We found that NFP staff and providers in this study also perceived collaboration to be necessary especially for families with the greatest number of psychosocial and medical risk factors; this is true also in the international NFP context (Jack et al, 2021;Li et al, 2015).…”
Section: Care Coordination As a Function Of Relational And Structural...mentioning
confidence: 56%
“…Specifically in women's care, midwives and health visitors perceive collaboration to be useful across the continuum of service delivery from antenatal care to postnatal care (Aquino et al, 2016). We found that NFP staff and providers in this study also perceived collaboration to be necessary especially for families with the greatest number of psychosocial and medical risk factors; this is true also in the international NFP context (Jack et al, 2021;Li et al, 2015).…”
Section: Care Coordination As a Function Of Relational And Structural...mentioning
confidence: 56%
“…Although nurses clearly understood the mandated requirement to make a child notification if there is a risk to the child and made notifications when required, they regretted losing trust when a notification was made. Nurses recognised that damage to the relationship between the nurse and the client could limit future disclosure of abuse, as described in other research (Davidov et al, 2012;Jack et al, 2021). Nurses spoke of balancing risk and relationship, traversing this practice thread as the woman's situation changed and risk was reassessed.…”
Section: Discussionmentioning
confidence: 95%
“…For women who disclose and are not ready to act, informational support is most effective, coupled with emotional support (Jack et al, 2021). Nurses are in a position of privilege with the women, and EMCH nursing work requires reflective practice, acknowledging this imbalance of power.…”
Section: Discussionmentioning
confidence: 99%
“…Local governments should provide effective maternal and child healthcare services and systems to prevent child maltreatment (WHO, 2019). Public health nurses (PHNs) play a crucial role in supporting newborns and their parents and developing family‐friendly healthcare systems to prevent child maltreatment in community settings (Jack et al., 2021). Studies have shown that characteristics of mothers at high risk for child maltreatment include poor mental health conditions, being of a young age, and having been abused as a child (Bayrampour et al., 2016; Cammack et al., 2018; Hovdestad et al., 2015; Thombs et al., 2020).…”
Section: Introductionmentioning
confidence: 99%